2017
DOI: 10.7863/ultra.16.07054
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Sonographic Assessment of the Quadriceps Femoris Muscle in Healthy Japanese Adults

Abstract: Sonography has the capacity to quantitatively assess muscular morphologic changes due to aging and could be a valuable tool for early detection of musculoskeletal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 29 publications
3
21
1
Order By: Relevance
“…To reflect both the quantitative and qualitative changes, skeletal muscles in the elderly show characteristic imaging features. Recently, Watanabe and colleagues reported correlations between physical characteristics (age, height, weight, body mass index, muscle strength) and several texture features (mean, skewness, kurtosis, inverse difference moment, angular second moment, and sum of entropy) in healthy adults (12). Our study is in line with the study by Watanabe and colleagues to show age-dependency in some of the texture features.…”
Section: Texture Features and Agesupporting
confidence: 92%
See 2 more Smart Citations
“…To reflect both the quantitative and qualitative changes, skeletal muscles in the elderly show characteristic imaging features. Recently, Watanabe and colleagues reported correlations between physical characteristics (age, height, weight, body mass index, muscle strength) and several texture features (mean, skewness, kurtosis, inverse difference moment, angular second moment, and sum of entropy) in healthy adults (12). Our study is in line with the study by Watanabe and colleagues to show age-dependency in some of the texture features.…”
Section: Texture Features and Agesupporting
confidence: 92%
“…However, before reliably using muscle texture features in any clinical settings, these should be carefully assessed in the confounding factors, such as gender and aging. Watanabe and colleagues recently showed that there was indeed aging effects in the muscle texture features, although they analyzed only 6 texture features (12). Our study is in agreement with the study by Watanabe and colleagues and further extended the classes of texture features.…”
Section: Clinical Indicationsupporting
confidence: 92%
See 1 more Smart Citation
“…Another concern is that EI is affected by the thickness of tissues and by the US scanner settings. 64 Contrary to a conventional first-order statistical feature like EI (histogram analysis), second order or higher order texture analyses have little effect on change by gain or frequency and intensity invariant. 64,65 Texture analysis provides an objective quantitative assessment of tissue heterogeneity by analyzing the distribution and relationship of pixel gray levels in the image, 66 so its application can effectively overcome these limitations.…”
Section: Echo Intensitymentioning
confidence: 99%
“…64 Contrary to a conventional first-order statistical feature like EI (histogram analysis), second order or higher order texture analyses have little effect on change by gain or frequency and intensity invariant. 64,65 Texture analysis provides an objective quantitative assessment of tissue heterogeneity by analyzing the distribution and relationship of pixel gray levels in the image, 66 so its application can effectively overcome these limitations. Texture analysis of muscle recently enabled differentiation between normal and pathologic muscles, suggesting that texture analysis may be a promising tool for differentiation of various muscle diseases.…”
Section: Echo Intensitymentioning
confidence: 99%